Evaluation of Antioxidant, Anti-inflammatory and Antimicrobial Activities of the Leaf Extracts of Luffa cylindrica: A Comprehensive Review - Salma Nassir Alquraish et al. (International Journal of Scientific Research and Innovative Studies, 2025)
Luffa cylindrica (L.) Roem, commonly known as sponge gourd or loofah, is a Cucurbitaceous plant widely distributed across tropical and subtropical regions of Asia and Africa. Traditionally employed in various ethnomedicinal systems for treating inflammation, pain, microbial infections, and metabolic disorders, the species has garnered significant scientific attention over the past decade. This comprehensive review synthesizes current knowledge on the phytochemical composition and pharmacological activities of L. cylindrica leaf extracts, with particular emphasis on antioxidant, anti-inflammatory, and antimicrobial properties. Accumulating evidence demonstrates that leaf extracts contain diverse bioactive secondary metabolites, including flavonoids (myricetin, apigenin-7-glucuronide, luteolin-7-O-β-D-glucuronide methyl ester), phenolic compounds (ferulic acid, p-coumaric acid, gallic acid, caffeic acid, chlorogenic acid), triterpenoids (oleanolic acid, echinocystic acid, lucyosides A-M), saponins, carotenoids (β-carotene), and steroids, with quantitative composition varying according to geographical origin, extraction solvent, and plant part utilized. Antioxidant activity has been consistently documented through DPPH, chelating effect, hydroxyl radical, and superoxide anion scavenging assays, with IC50 values ranging from 54.41 to 90 μg/mL depending on extract type and provenance. Anti-inflammatory effects are mediated through multiple mechanisms, including inhibition of nitric oxide and prostaglandin E2 production, suppression of pro-inflammatory cytokines (IL-6), downregulation of iNOS and COX-2 expression, and modulation of AKT-GSK3β-CREB, NF-κB, and AP-1 signaling pathways. Antimicrobial studies reveal selective activity against Gram-positive bacteria (Bacillus subtilis, Staphylococcus aureus) and certain Gram-negative organisms (Escherichia coli, Salmonella typhi), with minimum inhibitory concentration values ranging from 12.5 to 100 mg/mL, while antifungal effects appear negligible. Recent investigations have also identified novel applications in neuroinflammation, cognitive impairment, oral carcinoma, hepatocellular carcinoma, and breast cancer through apoptosis modulation and cancer stem cell targeting. Emerging toxicological data indicate moderate toxicity at high doses (4000 mg/kg), necessitating dosage consideration. This review identifies significant research gaps, including limited standardized clinical trials, insufficient mechanistic elucidation of individual phytochemicals, incomplete structure-activity relationships, and the need for comprehensive bioavailability studies, while proposing directions for future translational research. Keywords: Luffa cylindrica, leaf extracts, antioxidants, anti-inflammatory agents, antimicrobial activity, phytochemicals, flavonoids, myricetin, ferulic acid, oleanolic acid, neuroinflammation Received Date: October 20, 2025 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/574